Assessment of Identity Disturbance: Factor Structure and Validation of the Personality Structure Questionnaire in an Italian Sample - Berrios-Espinoza, R (American Psychological Association Inc., 2016)
There are few brief measures of identity disturbance for use in clinical practice that have been subject to any cross-cultural validation. This study investigated the construct validity of the Personality Structure Questionnaire (PSQ) in Italian clinical (N = 237) and community (N = 296) samples. Confirmatory factor analysis was conducted to investigate the internal structure of the PSQ. A 3-factor structure (i.e., differing self-states, mood variability, and behavioral loss of control) including a second-order factor provided the best fit to the data. This structure was demonstrated to be invariant across sex and clinical diagnosis, with clinical diagnosis significantly predicting increased PSQ scores. A global PSQ score of between 26 and 28 was found to be an appropriate cutoff for assisting in diagnostic processes. The clinical implication of the study is that quantitative assessment of identity disturbance can be rapidly achieved via the PSQ, usefully supplementing necessary diagnostic and formulation work. © 2015 American Psychological Association.